2022
DOI: 10.14210/rtva.v24n2.p270-294
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura enoturística do Vale dos Vinhedos: uma análise a partir da oferta

Abstract: As novas tendências globais de consumo e transformações nas sociedades agroindustriais têm imposto novos desafios às economias vigentes. Buscando por maior competitividade, os atores do setor do vinho têm investido na diversificação e diferenciação de seus produtos por meio de estratégias como o turismo. No entanto, a incorporação do turismo em territórios típicos da produção vitivinícola, favorece a competição por espaço e recursos naturais, colocando em risco a atividade principal. Assim, o presente trabalho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Despite the many concepts and definitions for the term wine tourism, it can be understood as the tourist practice to the attractions available in the grape and wine producing regions, where wine and the identity of the wine regions are the main motivating elements for visitors (Carlsen, 2004;Hall, 2004;Getz;Brown, 2006;Valduga, 2012;Falcade, 2016;Bruch;Bettencourt, 2022). Although it cannot be considered a recent activity, it was only in the last three decades that wine tourism emerged as a fundamental practice for wine territories, especially in the New World of Wine's countries such as Brazil, Uruguay, Chile, and Argentina.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the many concepts and definitions for the term wine tourism, it can be understood as the tourist practice to the attractions available in the grape and wine producing regions, where wine and the identity of the wine regions are the main motivating elements for visitors (Carlsen, 2004;Hall, 2004;Getz;Brown, 2006;Valduga, 2012;Falcade, 2016;Bruch;Bettencourt, 2022). Although it cannot be considered a recent activity, it was only in the last three decades that wine tourism emerged as a fundamental practice for wine territories, especially in the New World of Wine's countries such as Brazil, Uruguay, Chile, and Argentina.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its pioneering spirit in the country, its important wineries, and the fact that it receives a large number of tourists throughout the year, Vale dos Vinhedos has established itself as a reference for brazilian wine tourism Lindner, 2018). Since then, several studies have been carried out in the region, focusing on its history (Valduga, 2012), culture (Zanini;Rocha, 2010;Lindner, 2018), gastronomy (Silva et al, 2016), organization Bruch;Bettencourt, 2022), visitation practices (Tonini;Levandoski, 2011;Bellé et al, 2022) and affective image of tourists (Freire et al, 2023). However, no studies were found that sought to understand the relationships between the practice of wine tourism and Sustainable Territorial Development (STD) from the perspective of local actors, especially residents.…”
Section: Introductionmentioning
confidence: 99%